A novel, double mutation in DNA gyrase A of Escherichia coli conferring resistance to quinolone antibiotics. - Truong, Q C (1997)
A spontaneous Escherichia coli mutant, named Q3, resistant to nalidixic acid was obtained from a previously described clinical isolate of E. coli, Q2, resistant to fluoroquinolones but susceptible to nalidixic acid (E. Cambau, F. Bordon, E. Collatz, and L. Gutmann, Antimicrob. Agents Chemother. 37:1247-1252, 1993). Q3 harbored the mutation Asp82Gly in addition to the Gly81Asp mutation of Q2. The different mutations leading to Gly81Asp, Asp82Gly, and Gly81AspAsp82Gly were introduced into the gyrA gene harbored on plasmid pJSW102, and the resulting plasmids were introduced into E. coli KNK453 (gyrAts) by transformation. The presence of Asp82Gly or Gly81Asp alone led to a low-level resistance to fluoroquinolones but not to nalidixic acid resistance. When both mutations were present, resistance to both nalidixic acid and fluoroquinolones was expressed. Purified gyrases of the different mutants showed similar rates of supercoiling. Dominance of the various gyrA mutant alleles harbored on plasmids was examined. The susceptibility to quinolones associated with wild-type gyrA was always dominant. The susceptibility to nalidixic acid expressed by the Gly81Asp mutant was dominant, while that expressed by the Asp82Gly mutant was recessive. From these results, we hypothesize that some amino acids within the quinolone resistance-determining region of gyrase A are more important for the association of subunits rather than for the activity of the holoenzyme.